Healing developmental trauma eaudiobook How early trauma affects self-regulation, self-image, and the capacity for relationship. - Heller, Laurence (Tantor Media, 2015)
Explaining that an impaired capacity for connection to self and to others underlies most psychological and many physiological problems, clinicians Laurence Heller, PhD, and Aline LaPierre, PsyD, introduce the NeuroAffective Relational Model™ (NARM), a unified approach to developmental, attachment, and shock trauma that emphasizes working in the present moment. NARM is a somatically based psychotherapy that helps bring into awareness the parts of self that are disorganized and dysfunctional without making the regressed, dysfunctional elements the primary theme of the therapy. It emphasizes a person's strengths, capacities, resources, and resiliency and is a powerful tool for working with both nervous system regulation and distortions of identity such as low self-esteem, shame, and chronic self-judgment.